Bending and cutting links hand tools / Zamali Omar, Ayu Wirdawati Po'a and Siti Marlinna Chu Mohd Rizal Chu - Omar, Zamali; Po'a, Ayu Wirdawati; Mohd Rizal Chu, Siti Marlinna Chu (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Bending and Cutting Link Hand Tools is a product invented to measure, bend and cut the mild steel reinforcement bar to required size. The equipment usually used at site construction to bend and cut the bar mostly made by the workers by using nailed wooden board. This board can't be reusable in because it easily rotten. The separated process of cutting and bending also contribute to material and labour wastage. By using the Bending and Cutting Link Hand Tools, the process of cutting and bending reinforcement bar is easier, effective and safe: